Flow-volume loop abnormality detecting a previously unrecognized right upper lobe tracheal bronchus. (2015) - Ruzycki, Shannon; Tsai, Willis H.; Davidson, Warren J.
Abstract: Tracheal bronchus is a rare anatomic variant in which a bronchus originates from the trachea. Patients may be asymptomatic or present with a variety of respiratory symptoms. We present a case of a patient who presented with a history of poorly controlled asthma and a persistent abnormality of the flow-volume loop. Bronchoscopy revealed a tracheal bronchus with narrowed right-sided bronchial orifices. An unrecognized tracheal bronchus may result in serious complications during elective or emergent endotracheal intubation. Spirometry testing may reveal abnormalities of the flow-volume loop associated with altered airflow. Relying on spirometric values without assessing the shape of the flow-volume loop may lead to misdiagnosis and inappropriate management of lung pathology.